Active human full-length CDKL5 produced in the Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 - Colarusso A.; Lauro C.; Calvanese M.; Parrilli E.; Tutino M. L. (Microbial Cell Factories, 2022)
Background: A significant fraction of the human proteome is still inaccessible to in vitro studies since the recombinant production of several proteins failed in conventional cell factories. Eukaryotic protein kinases are difficult-to-express in heterologous hosts due to folding issues both related to their catalytic and regulatory domains. Human CDKL5 belongs to this category. It is a serine/threonine protein kinase whose mutations are involved in CDKL5 Deficiency Disorder (CDD), a severe neurodevelopmental pathology still lacking a therapeutic intervention. The lack of successful CDKL5 manufacture hampered the exploitation of the otherwise highly promising enzyme replacement therapy. As almost two-thirds of the enzyme sequence is predicted to be intrinsically disordered, the recombinant product is either subjected to a massive proteolytic attack by host-encoded proteases or tends to form aggregates. Therefore, the use of an unconventional expression system can constitute a valid alternative to solve these issues. Results: Using a multiparametric approach we managed to optimize the transcription of the CDKL5 gene and the synthesis of the recombinant protein in the Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 applying a bicistronic expression strategy, whose generalization for recombinant expression in the cold has been here confirmed with the use of a fluorescent reporter. The recombinant protein largely accumulated as a full-length product in the soluble cell lysate. We also demonstrated for the first time that full-length CDKL5 produced in Antarctic bacteria is catalytically active by using two independent assays, making feasible its recovery in native conditions from bacterial lysates as an active product, a result unmet in other bacteria so far. Finally, the setup of an in cellulo kinase assay allowed us to measure the impact of several CDD missense mutations on the kinase activity, providing new information towards a better understanding of CDD pathophysiology. Conclusions: Collectively, our ...